Clarifying the role of clinical supervisors according to physiotherapists at a higher education institution - Taryn-Lee Voges; Josè M. Frantz (AOSIS, 2019)
Background: The roles of doctors and nurses in clinical supervision and clinical education are well defined. The role of the physiotherapist in clinical education has not been clearly defined. Objectives: The aim of this study was to define and clarify the views and experiences of physiotherapy clinical supervisors regarding clinical education and their role in contributing to student learning. Methods: This qualitative exploratory study targeted 17 physiotherapy clinical supervisors, employed in a physiotherapy department, at a local university in the Western Cape. Twelve of the 17 participants agreed to participate in the study. Data were collected by means of in-depth audio-taped interviews, at a time convenient for the participants. Each transcript was read individually by the first author and notes made in the margins to highlight interesting concepts that emerged. The different types of concepts were listed and categorised, while common categories were grouped into themes. Results: Based on the results, the clinicians' role is viewed as a valuable asset in clinical education, embodying the role of an educator, mentor, role model and communicator. Clinical supervisors discussed their roles in terms of understanding the importance of clinical supervision, providing guidance within a clinical setting, role modelling and professionalism. Although clinical supervisors play a significant role, they experienced a few challenges including role clarification and students' lack of knowledge. Conclusion: This study highlights that clinical supervisors and clinicians fulfil significant roles in assisting students to integrate theoretical and clinical knowledge. Clinical implications: Understanding the expectations of clinical supervisors in supporting clinical education is important for higher education institutions and the clinical sector.